Tanggung Jawab Hukum Pengelola Pelabuhan terhadap Keselamatan Penumpang dalam Angkutan Penyeberangan - Abdul, Deni S.M; Moonti, Roy Marthen; Ahmad, Ibrahim (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Passenger safety in ferry transportation is a crucial issue in Indonesia's sea transportation system, especially due to the high rate of accidents caused by the negligence of port managers. This study aims to analyze the form and limit of port manager's legal responsibility for passenger safety based on national regulations and international legal instruments. This research uses a normative method with the approach of legislation, legal doctrine, and court decisions. The results of the study show that port managers have administrative, civil and criminal responsibilities for passenger safety, including moral and social responsibilities. Failure to carry out these obligations can lead to legal sanctions. It is recommended that port managers strengthen safety management systems, improve inter-agency coordination, and adopt technology and good governance principles to ensure optimal legal protection for passengers. Regulatory updates and continuous supervision are also indispensable.